Answer:
right 4 units
Explanation:
The reflection across x=2 makes the transformation ...
(x, y) ⇒ (4 -x, y)
The reflection across x=0 makes the transformation ...
(x, y) ⇒ (-x, y)
The two transformations together make the transformation ...
(x, y) ⇒ (-(4-x), y) = (x -4, y)
To get the original point back, we need the translation ...
(x, y) ⇒ (x +4, y) . . . . . translate right 4 units
_____
Check
That, together with the original pair of reflections gives ...
(x, y) ⇒ ((x -4) +4, y) = (x, y) . . . the original point